Enhancing the use of impact evaluation results: a multi-case study in agricultural research organizations - Daniela Maciel Pinto; Adriana Bin (Revista de Economia e Sociologia Rural)
Abstract Impact evaluation has historically been the primary method for assessing agricultural research. However, the practical use of its results remains underexplored in the literature. Addressing this gap, this study investigates the use of impact evaluation results in agricultural RD&I organizations through a multi-case analysis of eight organizations across three continents. Grounded in the social responsibility and ethics of research and evaluation, this study addresses the question: “How are impact evaluations in agricultural RD&I organizations conducted, and how are their results utilized to enhance strategic decision-making and innovation?” To answer this question, the AGRIUM model was developed and applied, focusing on objectives, methods, impact dimensions, uses, and stakeholders. The findings indicate that neither experience with evaluations nor the diversity of evaluated dimensions directly influence the utilization of results. Instead, three categories of factors emerged: (1) structural and organizational, such as integration into strategic planning; (2) operational, including evaluation quality, communication, and timeliness; and (3) team literacy and stakeholder pressures. Establishing a well-defined process, including information management, documentation, feedback practices, and monitoring recommendations, was identified as critical not only for driving impactful agricultural research but also for informing policy decisions and strengthening institutional strategies.